Penerapan Model Problem Based Learning (PBL) dan Gaya Belajar Siswa Secara Interaksi Meningkatkan Kemampuan Memecahkan Soal Cerita Matematika dari Perspektif Aksiologi dalam Filsafat Ilmu - Ardianik, Ardianik; Masitoh, Siti; Nursalim, Mochamad (Universitas Dr. Soetomo, 2022)
The concept of axiology in the philosophy of science, namely the implementation of knowledge that has been learned from mathematics, turns out to have enormous benefits for everyone, especially in efforts to solve cases related to real life which are applied in the form of mathematical story problems through the PBL model. The purpose of this study was to prove: (1) students' ability to solve word problems based on learning styles; (2) students' ability to solve word problems between those implementing the conventional model and the PBL model; (3) the effect of interaction between learning models and learning styles on students' ability to solve word problems. This research is based on quantitative with experimental type. This experiment was conducted by the same teacher on a system of three variable linear equations, 90 minute sessions twice a week for three weeks. Class X-1 and class X-3 as research samples. The data collection method used a 5-item essay test and a learning style questionnaire. Hypothesis testing is processed using Two-Way Anova. The results showed (1) there was a very significant difference in the ability to solve word problems based on students' learning styles (visual, auditory, and kinesthetic); 2) there is a significant difference in the ability to solve word problems between those who apply the conventional model and the PBL model; 3) there is an interaction effect between learning styles and learning models that is significant on the ability to solve word problems in class X SMA Dr.Soetomo Surabaya. Keywords: Learning Style, Problem Based Learning (PBL), Math Story Problems